The Impact of Sarcopenic Obesity on Weight Loss Outcomes and Recurrent Weight Gain Following Laparoscopic Sleeve Gastrectomy - Wang X; Shu X; Pei W; Yuan C; Su X; Xiong J; Chen W; Zhang G; Jie Z; Liu Y (Diabetes, Metabolic Syndrome and Obesity, 2025)
Xiaoqiang Wang,1,* Xufeng Shu,1,* Wenguang Pei,2,* Chendong Yuan,1 Xujie Su,1 Jianbo Xiong,1 Wenzheng Chen,1 Guoyang Zhang,1 Zhigang Jie,1 Yi Liu1 1Department of General Surgery, the First Affiliated Hospital, Jiangxi Medical College, Nanchang University, Nanchang, 330000, People’s Republic of China; 2Department of Abdominal Tumor Surgery, Jiangxi Cancer Hospital, Nanchang, 330000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhigang Jie, Email ndyfy00524@ncu.edu.cn Yi Liu, Email ndyfy01913@ncu.edu.cnBackground: Sarcopenic obesity (SO) presents a significant public health challenge. Although the prevalence of SO is on the rise, there is a notable paucity of research examining the impact of SO on weight loss efficacy following laparoscopic sleeve gastrectomy (LSG).Purpose: To investigate the impact of SO on weight loss outcomes and recurrent weight gain following LSG.Methods: We retrospectively gathered clinical data of 104 patients with obesity who underwent LSG in our hospital between January 2020 and September 2023. The ratio of fat mass to lean mass ≥ 0.8 was calculated for SO. Among them, the SO group (n=34) and the non-sarcopenic obesity (NSO) group (n=70), and the effect of SO on weight loss outcomes and recurrent weight gain were comparatively analyzed.Results: Within one year after LSG, SO patients had an apparently higher average body mass index, excess body mass index, and lower average percentage of excess weight loss than NSO patients (P< 0.05). Furthermore, NSO patients had a statistically striking optimal weight loss rate more than SO patients in the first year after surgery (58.6% vs 35.3%, P=0.026). Within two years after LSG, SO patients had a lower occurrence rate of recurrent weight gain than NSO patients. Nonetheless, this difference was not statistically significant (P=0.212). Additionally, diabetes was an independent risk factor for recurrent weight gain postoperatively in patients with obesity when both univariate and multivariate analyses were conducted (P< 0.05).Conclusion: SO adversely affects short-term weight loss outcomes after LSG. However, the effect of SO on postoperative recurrent weight gain was not statistically significant, indicating that further research is needed. Furthermore, diabetes is an independent risk factor for postoperative recurrent weight gain in patients with obesity.Keywords: sarcopenic obesity, laparoscopic sleeve gastrectomy, weight loss outcomes, postoperative recurrent weight gain, risk factors